Factors Affecting Employee Engagement at Sharia Hotels - Raden Bambang Budhijana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Employee engagement is closely related to human resources in the organization and is an Islamic human capital.  Employee engagement is also needed by the tourism industry, namely employees in sharia hotels. These employees have an important role in the success of Sharia Hotels to satisfy consumers if the employee's attachment to the company is high.  This study uses several variables including leadership, financial compensation and organizational Behavior that is suspected of affecting employee engagement.  Data collection was carried out using an online survey questionnaire covering 93 respondents and processed regression using SPSS.  The results show that leadership, financial compensation, and organizational behavior have a positive effect on employee engagement based on statistics testing.